ANALYSIS OF CHANGES IN FOREST AREAS BASED ON REMOTE SENSING DATA: (on the example of Syunik Region) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Remote sensing technologies provide an effective means of monitoring forest ecosystem changes without the need for direct field observations. This study investigates changes in forested areas of the Syunik Region, focusing on the impacts of forest fires, illegal logging, and tailings dumps. SENTINEL-2 satellite imagery was processed and analyzed using the Normalized Burn Ratio (NBR), Normalized Difference Vegetation Index (NDVI), and Normalized Difference Moisture Index (NDMI) to detect and quantify vegetation loss and degradation over different time periods. Comparative analysis of multi-temporal satellite data revealed significant alterations in forest cover, highlighting the effectiveness of remote sensing methods for detecting deforestation trends and assessing environmental consequences. The findings underscore the importance of satellite-based monitoring for sustainable forest management and conservation efforts.
Keywords: remote sensing; forest monitoring; deforestation; wildfires; vegetation indices; environmental impact assessment; NBR; NDVI